Assessment of physical, technical, and tactical analysis in the Australian Football League: A systematic review - Vella, A.; Clarke, A. C.; Kempton, T.; Ryan, S.; Couttsm, A. J. (Sports Medicine - Open, 2022)
Key Points - Match running requirements are reliant on numerous technical and tactical contextual factors that are uniquely dependent on the team, opposition, and the AFL season/s in which the study was conducted (e.g. rule changes).